A New Animal Model of Thrombophilia Confirms that High Plasma Factor VIII Levels Are Thrombogenic - Kawasaki, Tomihisa; Kaida, Takehiro; Arnout, Jef; Vermylen, Jos; Hoylaerts, Marc F. (Thrombosis and Haemostasis, 1999)
The thrombotic risk associated with elevated plasma levels of clotting factor VIII (FVIII) was investigated in a mouse model of thrombophilia. After the intravenous injection of recombinant human FVIII and/or of purified FVIII-free human von Willebrand factor (vWF), a controlled mild injury was inflicted on the carotid artery of FVB mice by irradiation with filtered green light in combination with intravenous injection of the dye rose bengal. Formation of a platelet-rich thrombus was continuously monitored for 40 min via transillumination and the thrombus size was measured via image analysis. Administration of recombinant human FVIII at 40 g/kg led to initial FVIII plasma activities equivalent to 250% of normal human plasma FVIII activity and significantly enhanced thrombus size. Immunohistochemical staining illustrated the accumulation of FVIII within the thrombi. Human vWF, even at 10 mg/kg, had no effect on thrombus formation. The thrombotic tendency induced by FVIII was significantly inhibited by the administration of human vWF in a dose-dependent manner. Separate plasma measurements revealed that human FVIII has comparable affinities for human and murine vWF but that human vWF does not effectively bind murine platelets. The inhibition by human vWF of the thrombotic tendency induced by human FVIII could therefore be explained by a lack of accumulation of FVIII within the developing thrombus because of the reduced affinity of human vWF for murine platelets and the reduced occupancy of murine von Willebrand factor by human FVIII after injection of human vWF. These results show that vWF actively participates in FVIII accumulation in the arterial thrombus and provide experimental evidence for epidemiological findings that elevated plasma FVIII levels are associated with an increased thrombotic risk, also in arteries.